2013
DOI: 10.1177/1538574413500538
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Allogeneic Blood Products With Routine Use of Autotransfusion in Open Elective Infrarenal Abdominal Aortic Aneurysm Repair

Abstract: The rIAT reduced the exposure to allogeneic blood products by more than 50%, in particular for patients with AAA larger than 60 mm. These results support the use of rIAT for open elective infrarenal AAA repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Previous studies of patients undergoing AAA have shown significant reductions in allogeneic blood exposure with the use of ICS (Courtemanche et al ., ; Pasternak et al, ). However, none have shown such a large case series with total avoidance of blood products unless the pre‐operative haemoglobin concentration was already below 106 g L −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of patients undergoing AAA have shown significant reductions in allogeneic blood exposure with the use of ICS (Courtemanche et al ., ; Pasternak et al, ). However, none have shown such a large case series with total avoidance of blood products unless the pre‐operative haemoglobin concentration was already below 106 g L −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ICS for AAA reduces the need for allogeneic red cells by more than 50%, and possibly attenuates the incidence of post‐operative SIRS and infection (Shantikumar et al ., ; Tavare & Parvizi, ). The reduction in allogeneic transfusion is particularly relevant for patients with aneurysmal diameter greater than 60 mm (Courtemanche et al ., ).…”
mentioning
confidence: 99%
“…Se realiza mediante la recolección de sangre recuperada del campo operatorio o de un circuito extracorpóreo. Está contraindicado en caso de padecer el paciente infección o neoplasia, así mismo no podrá realizarse si se utilizan soluciones yodadas sobre el campo quirúrgico o si se produce contaminación del mismo 184 .…”
Section: Recuperación Intra Y Postoperatoriaunclassified